1995
DOI: 10.1177/0093854895022003006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “Fixed Propensity” to Commit Sexual Offenses

Abstract: The concept of “fixed emotional propensity” was explored by evaluating 62 sexual offenses committed by 23 male repeat offenders. Two general clusters of sex offenders were discerned, that is, more aggressive versus less aggressive offenders. In addition, sexual offenses committed by the same offender were much more similar than those committed by different offenders. The more similar the offense pattern, the greater the number of alleged offenses. In general, the results indicated that fixed emotional propensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In other words, crime switching should be expected in the first few arrests, whereas crime specialisation should be found for more prolific offenders. In line with such a statement, a study conducted by Beutler et al () demonstrated that a more similar offence pattern throughout the offender's crime series was associated with a greater number of alleged offences. Other studies also found that specialisation for specific types of offences was more likely for more ‘experienced’ and prolific offenders (Blumstein et al, ; Lussier, Bouchard, & Beauregard, ).…”
Section: Criminal Career and Crime Specialisationmentioning
confidence: 86%
See 1 more Smart Citation
“…In other words, crime switching should be expected in the first few arrests, whereas crime specialisation should be found for more prolific offenders. In line with such a statement, a study conducted by Beutler et al () demonstrated that a more similar offence pattern throughout the offender's crime series was associated with a greater number of alleged offences. Other studies also found that specialisation for specific types of offences was more likely for more ‘experienced’ and prolific offenders (Blumstein et al, ; Lussier, Bouchard, & Beauregard, ).…”
Section: Criminal Career and Crime Specialisationmentioning
confidence: 86%
“…By using different methodological and analytical strategies, studies' results indicate that offences committed by the same offender show greater similarity than crimes committed by different offenders (e.g. Beutler, Hinton, Crago, & Collier, ; Lundrigan et al, ; Santtila, Junkkila, & Sandnabba, ). Prior studies also revealed that it is possible to successfully distinguish between linked and unlinked crimes on the basis of the offender's behaviours displayed at the crime scene (e.g.…”
Section: Criminal Career and Crime Specialisationmentioning
confidence: 99%
“…An abundance of research evidence from the personality arena, therefore, addresses the existence of behavioural consistency. Indeed, much research now exists showing cross-situational consistency in both non-criminal (Funder & Colvin, 1991;Furr & Funder, 2004;Shoda, Mischel, & Wright, 1993, 1994Wright & Mischel, 1987) and criminal behaviour, including stranger sexual crimes against both adults and children (Beutler, Hinton, Crago, & Collier, 1995;Canter et al, 1991, cited in Woodhams & Toye, 2007Grubin, Kelly, & Ayis, 1997;Grubin, Kelly, & Brunsdon, 2001;Knight, Warren, Reboussin, & Soley, 1998;Santtila, Junkkila, & Sandnabba, 2005), homicide (Salfati & Bateman, 2005), arson (Santtila, Fritzon, & Tamelander, 2005), residential and commercial burglary (Bennell & Canter, 2002;Bennell & Jones, 2005;Green, Booth, & Biderman, 1976;Yokota & Canter, 2004), and commercial robbery (Woodhams & Toye, 2007).…”
Section: The Principles Of Case Linkagementioning
confidence: 99%
“…Another approach that makes use of techniques able to take into account the interaction of a number of variables is described in a preliminary report by Beutler, Hinton, Crago & Collier (1995). They refer to the fixed propensities of an individual to behave in certain ways, which is in effect another way of referring to behavioural consistency.…”
Section: Fixed Propensitiesmentioning
confidence: 99%